Membership in a diabetes-care network and adherence to clinical practice guidelines for treating type 2 diabetes among general practitioners: A four-year follow-up. Issue 5 (October 2016) - Casanova, Ludovic; Bocquier, Aurélie; Cortaredona, Sébastien; Nauleau, Stève; Sauze, Laurent; Sciortino, Vincent; Villani, Patrick; Verger, Pierre
Highlights: General practitioners belonging to diabetes care networks adhered more closely to diabetes care guidelines. Results were clinically relevant only for HbA1C and microalbuminuria assays. This improvement benefited all patients with diabetes, not only with the network patients. Results suggest existence of a halo effect. Abstract: Objectives: To assess whether private general practitioners (GPs) belonging to a diabetes-care network adhered more closely to clinical practice guidelines for diabetes care than GPs not in such a network, for all their patients with type 2 diabetes treated with medication (patients with diabetes), regardless of whether they received care through a network (that is, whether a halo effect occurred). Research design and measures: The study, based on health insurance reimbursement databases in southeastern France, included 468 GPs in two networks and 468 non-network GPs in the same geographical area, matched one-to-one by propensity scores. We followed up their patients with diabetes ( n  = 22, 808) from 2008 through 2011, conducting multivariate time-to-event analyses (Cox models) that took the matching design into account to evaluate time from inclusion until performance of the given number of each of six recommended examinations/tests. Results: GPs belonging to a diabetes-care network adhered more closely to clinical practice guidelines but our result were slightly pronounced. Hazard ratios (HR) were significantly higher for patients of network GPs for the implementation of 3 HbA1C assays (HRa = 1.13; [95%CI = 1.10–1.16]), or 1 microalbuminuria assay (1.4 [1.35–1.45]); they were lower for LDL-cholesterol assays (1.04 [1.01–1.07]) and ophthalmological checkups (1.07 [1.04–1.10]), and not significant for creatinemia or cardiac monitoring. Conclusions: Network GPs had better diabetes monitoring practices for all their patients with diabetes than the other GPs, especially for the most diabetes-specific tests. Further research is needed in other settings to confirm the existence of this halo effect.